Dietary effects of a mix derived from oregano (Origanum vulgare L.) essential oil and sweet chestnut (Castanea sativa Mill.) wood extract on pig performance, oxidative status and pork quality traits. (February 2015) - Ranucci, D.; Beghelli, D.; Trabalza-Marinucci, M.; Branciari, R.; Forte, C.; Olivieri, O.; Badillo Pazmay, G.V.; Cavallucci, C.; Acuti, G.
Abstract: The effects of a pre-formulated commercial plant extract mix, composed of equal parts of oregano essential oil and sweet chestnut wood extract, on performance, oxidative status and pork quality traits were evaluated. In two 155-d studies, 60 pigs (mean live weight: 42.9 kg) were assigned to either a control diet (CTR) or an identical diet supplemented (0.2%) with the plant extract mix (OC). No differences in the growth rate were observed. Glutathione peroxidase and glutathione reductase activities in the OC muscles ( Longissimus lumborum ) were higher than in CTR muscles. The lipid oxidation of meat was lower in the OC group. In the cooked meat samples, OC animals had the lowest L* and H° values and the highest a* values. The OC meat received higher scores for colour, taste and overall liking in both the blind and the labelled consumer tests. Highlights: The dietary oregano oil and sweet chestnut extract mix did not affect pig ADG. The mix increased serum antioxidant potential and reduced pork lipid oxidation. The mix was responsible for a darker and redder colour of the cooked meat. The pork sensory properties were improved by the plant extract mix.